Oil palm shell kernel in cement board (opscb) / M.F Ahmad … [et al.] - M.F, Ahmad; A., Ibrahim; M., Awang; W.B., Wan Nik; S., Sumazly; A.A. K., Hamidi (2002)
A wide variety of agricultural by-products are presently used, or is potentially usable in construction. Such by-product from the agricultural industry, oil-palm plantation being one of them, include palm shell kernel, empty fruit bunches, pressed fruit fibres, and frond. However it has been reported that these by-products are being hauled away as solid waste to landfills. Growing scarcity of dumping sites and coupled with stricter regulations of dumping practices have led to the use of a substantial proportion of these byproducts in construction. In an attempts to exploit the benefits of waste solid management via recycling and reusing of solid waste, an experimental programme was established to look into the prospect of incorporating ground oil-palm shells as 'aggregates' into cement-based composites. Cement-bonded particle boards were prepared and tested to BS 5669. Variations in the mixes were the the total water content and the 'aggregate - to - cement ratio. Preliminary studies revealed figures in the range of 2.90 6.3 Mpa are obtainable for the bending strength (or. Modulus of Rupture) of the boards with the total water content of between 35 to 45 percent of the total weight of dry materials and the 'aggregate '-tocement ratio of between 1:2.5 to I: 3. 5. Dimensional stability of the boards was also reported.